2021
DOI: 10.1093/bbb/zbab023
|View full text |Cite
|
Sign up to set email alerts
|

Mice derived from in vitro αMEM-cultured preimplantation embryos exhibit postprandial hyperglycemia and higher inflammatory gene expression in peripheral leukocytes

Abstract: We examined whether peripheral leukocytes of mice derived from in vitro-αMEM cultured embryos and exhibiting type 2 diabetes had higher expression of inflammatory-related genes associated with the development of atherosclerosis. Also, we examined the impact of a barley diet on inflammatory gene expression. Adult mice were produced by embryo transfer, after culturing two-cell embryos for 48 h in either α-MEM (minimal essential media) or KSOM (potassium simplex optimized medium) control media. Mice were fed eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…In a previous study, we demonstrated that mice derived from embryos cultured in MEM exhibit T2DM and high postprandial inflammatory gene expression in peripheral leukocytes, compared to mice derived from embryos cultured in potassium simplex-optimized medium (KSOM) in vitro [ 6 ]. Furthermore, the expression of some inflammatory genes in peripheral leukocytes was reduced by feeding these mice a diet containing barley.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, we demonstrated that mice derived from embryos cultured in MEM exhibit T2DM and high postprandial inflammatory gene expression in peripheral leukocytes, compared to mice derived from embryos cultured in potassium simplex-optimized medium (KSOM) in vitro [ 6 ]. Furthermore, the expression of some inflammatory genes in peripheral leukocytes was reduced by feeding these mice a diet containing barley.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we used same MEM and KSOM mice produced by the Kiwa Laboratory Animal Co., Ltd. (Wakayama, Japan) to analyze the development of steatohepatitis. The MEM mouse model and KSOM control mice have been described previously [ 5 , 6 ]. Briefly, two-cell stage embryos were collected from the oviducts of female Institute of Cancer Research (ICR) mice after mating with male ICR mice, and cultured in either MEM (135–15175, Wako Pure Chemical Industries, Ltd., Osaka, Japan) or KSOM (ARK Resource, Kumamoto, Japan) control medium for 48 h. The compositions of the MEM and KSOM are shown in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that mice developed from embryos cultured in vitro in a-MEM (MEM mice) exhibit T2DM with postprandial hyperglycemia and non-alcoholic steatohepatitis, in contrast to mice developed from embryos cultured in vitro in potassium simplex optimized medium (KSOM) (23). Barley intake for 10 weeks ameliorated nonalcoholic steatohepatitis in MEM mice (21).…”
Section: Animalsmentioning
confidence: 99%
“…This animal study was approved by the Ethics Committee of the University of Yamanashi (approval number A30-24) and was performed according to the institutional animal experiment guidelines. The mice were decapitated, and samples were collected from one mouse at a time in the order of MR, MB, and KC to ensure that each group had similar mean dissection times (9:00 am-3:00 pm) (21,23). Kidney tissue samples were collected and weighed, and the right kidney tissues were snapfrozen in liquid nitrogen and stored at −80°C until use for qRT-PCR and western blotting.…”
Section: Animalsmentioning
confidence: 99%